Eksperimen Sosis Sayur Hasil Olahan Dari Sayur Brokoli (Broccoli) Dan Wortel (Daucus Carota L.) - Mochamad Rizal Umami; guntoro guntoro (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2017)
Sausage is mostly made of meat, fat, food binders, food filler, water, salt, and other seasonings. The most common meats used in making sausage are beef and chicken. The availability of the ingredient is one of the reasons in choosing the meat substances. Indeed, most people put beef and chicken on the top list of their favorite foods. Unfortunately, the price of meat is expensive. For that reason, there is a need to search precise substitutional substances for meat – the researcher occupied vegetables (broccoli and carrot) to substitute beef and chicken. Vegetable cost much more cheaply than meats. In addition, it is rich in nutrients. Further, the researcher conducted the research of quality requirement of vegetable sausage based on SNI 101-3820-1995. In making the sausage, the vegetables and the chicken were washed. Then the chicken was chopped off while the vegetable was sliced. The next step was boiling the vegetables and the chicken. After that, the chicken, vegetables and all the seasonings were mixed and mashed in order to get smooth dough. Measured amount of wheat flour, cornstarch, and other ingredients were, then, added to the processed materials and stirred thoroughly. The dough was put into dough sausage machine then push the dough to shape the sausage. The final step was to steam the sausage until it was well-cooked. The tests include organoleptic test, water content test, protein test, ash content test, carbohydrate test, fat test, microbiology test including E. Coli and mold test. The results of the tests are all good while the result of the carbohydrate test reach higher value than the standard.